BELA NEGARA SEBAGAI WUJUD PARTISIPASI PEMUDA DALAM MEMPERKUAT KETAHANAN NASIONAL - Zlyta Mutia; Nurhalisyah; Wanda Maharani; Muhamad Dasya Tri Andika; Tiara Vania Ramadhani; Bambang Yuniarto (ADMIN: Jurnal Administrasi Negara, 2026)
Defending the nation is the responsibility of all citizens, who play a strategic role in maintaining national integrity and resilience, especially amidst increasingly complex global and national threats. As a dominant and productive demographic, youth hold a crucial position as agents of change in the implementation of non-military national defense. However, low national awareness, the influence of globalization, digital disruption, and the rise of individualism are key challenges in increasing youth participation. This article aims to analyze the role of youth in non-military national defense and its implications for strengthening national resilience. This research uses a descriptive qualitative approach with a literature review method, drawing on sources from books, scientific journals, laws and regulations, and official documents. The results indicate that youth participation in education, social, cultural, and digital sectors contributes significantly to strengthening the nation's ideological and socio-cultural resilience. Therefore, strengthening youth-based national defense needs to be carried out in an integrated manner through civic education, cross-sector synergy, and the use of digital media to ensure sustainable national resilience.